Exploration of the etiology of single small subcortical infarctions using high-resolution vessel wall MRI - Li, Yutian; Feng, Quanzhi; Wang, Congcong; Zhang, Xianchang; Wan, Liang; Han, Tong (Frontiers in Neurology, 2023)
Objective: We aimed to explore imaging indicators for diagnosing the etiology of single small subcortical infarctions (SSI) using high-resolution vessel wall imaging (HR-VWI). Methods: Patients with acute isolated subcortical cerebral infarction were prospectively enrolled and were classified as large artery atherosclerosis (LAA), stroke of undetermined etiology (SUD), small artery disease (SAD). The infarct information, the cerebral small vessel disease (CSVD) score, morphological characteristics of the lenticulostriate arteries (LSAs), and plaque characteristics were compared between the three groups. Results: 77 patients were enrolled (30 LAA, 28 SUD and 19 SAD). The total CSVD score of the LAA (P = 0.001) and SUD groups (P = 0.017) was significantly lower than that of the SAD group. The number and total length of LSAs branches in the LAA and SUD groups were shorter than in the SAD group. Moreover, the total length laterality index (LI) of the LSAs in the LAA and SUD groups was greater than in the SAD group. The total CSVD score and LI of total length were independent predictor for SUD and LAA groups. The remodeling index of the SUD group was significantly higher than that of the LAA group (P = 0.002); positive remodeling was dominant in the SUD group (60.7%), whereas remodeling in the LAA group was primarily non-positive (83.3%). Conclusions: SSI with and without plaques on the carrier artery may have different modes of pathogenesis. Patients with plaques may also have a coexisting mechanism of atherosclerosis.